2020
DOI: 10.3390/plants9101379
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Qualitative and Quantitative Composition and Content of Phenolic Compounds in the Fruit of Introduced American Cranberry (Vaccinium macrocarpon Aiton)

Abstract: The aim of this study was to determine the composition and content of phenolic compounds in ethanol extracts of eight different cultivars of American cranberry (Vaccinium macrocarpon Aiton) fruit using spectrophotometric and UPLC-ESI-MS/MS analysis and to evaluate the antioxidant activity in vitro of these extracts. The highest total amount of phenolic compounds evaluated via Folin–Ciocalteu spectrophotometry was detected in American cranberry fruit samples of the ‘Bain’ clone, and the highest total amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
(54 reference statements)
0
20
1
Order By: Relevance
“…Quercetin and myricetin derivatives have similar absorption spectra with two maxima, and thus reference standards are necessary for the identification of the compounds [31]. In our study, we did not detect compounds identified by other investigators, such as myricetin-3-rhamnoside [30], quercetin-3-rutinoside [2,47,48], and kaempferol-3-glucoside [49], possibly due to a too-low concentration of these compounds in the tested matrix. Synapic acid (Rt 7.591 min) and trans-ferulic acid (Rt 7.374 min) were identified in the study, and their amounts in the studied American cranberry matrix were below the LOQ value.…”
Section: Specificitycontrasting
confidence: 65%
See 1 more Smart Citation
“…Quercetin and myricetin derivatives have similar absorption spectra with two maxima, and thus reference standards are necessary for the identification of the compounds [31]. In our study, we did not detect compounds identified by other investigators, such as myricetin-3-rhamnoside [30], quercetin-3-rutinoside [2,47,48], and kaempferol-3-glucoside [49], possibly due to a too-low concentration of these compounds in the tested matrix. Synapic acid (Rt 7.591 min) and trans-ferulic acid (Rt 7.374 min) were identified in the study, and their amounts in the studied American cranberry matrix were below the LOQ value.…”
Section: Specificitycontrasting
confidence: 65%
“…de Jussie family native to North America that are now widely cultivated in Europe as well [1]. Due to the effect of biologically active compounds of cranberry fruit and their use in the food industry, large cranberry plantations are grown in Lithuanian farms and private gardens [2,3]. The following groups of biologically active compounds have been identified in cranberry fruit: flavonols (quercetin and myricetin derivatives) [4], flavan-3-ols, anthocyanins [5], tannins, derivatives of phenolic acids, and triterpenoids [6].…”
Section: Introductionmentioning
confidence: 99%
“…The highest antioxidant activity according to the ABTS •+ method was observed at stage 1, i.e., 15.9-47.8% higher than at the other the stages (Table 6). On the other hand, previous studies reported a value of 170.68 µM TE/g DW in ripe Vaccinium macrocarpon Aiton fruits [43], which is only 0.5% higher than the antioxidant activity (ABTS) at stage 4 in Vaccinium stenophyllum. Similarly, the highest antioxidant activity according to the DPPH • method was observed at stage 1, i.e., 15.4-19.55% higher than in the rest of the stages (Table 6).…”
Section: Identification and Quantification Of Anthocyanins By Hptlcmentioning
confidence: 63%
“…American cranberry (Vaccinium macrocarpon) is rich in a wide variety of phytochemicals such as saccharides, carotenoids, phenolic acids, and flavonoids [33,34]. Fresh berries, raisins, and powdered extracts have been used as natural remedies to treat inflammatory and microbial processes.…”
Section: Nutraceuticals From Plant Extractsmentioning
confidence: 99%